Pendidikan Karakter Berbasis Kearifan Lokal pada Program Studi Pendidikan Bahasa dan Sastra Indonesia - Fitriyah, Lailatul; Suryani, Suryani; Febriyanto, Dedi (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2022)
Character education based on local wisdom is one character education model that is quite effective in shaping Indonesian human character. This study aims to describe the pattern of implementation of character education based on local wisdom in the Indonesian Language and Literature Education Study Program at Nurul Huda University. This research was field research conducted using qualitative methods. The results show that the Indonesian Language and Literature Education Study Program at Nurul Huda University implemented character education based on local wisdom in every learning activity. The local wisdom that forms the basis for character education is the local wisdom of the Islamic boarding school and the Komering culture. Character education is based on local wisdom reflected through the vision and mission, the learning process, and student activities under the auspices of the Study Program. Through the implementation of character education based on local wisdom, students of the Indonesian Language and Literature Education Study Program at Nurul Huda University are expected to become virtuous individuals of superior quality, dignified, and have a Pancasila spirit.